The limits of global health diplomacy: Taiwan’s observer status at the world health assembly - Herington, Jonathan C. C.; Lee, Kelley (My University, 2015)
In 2009, health authorities from Taiwan (under the name “Chinese Taipei”) formally attended the 62nd World Health Assembly (WHA) of the World Health Organization as observers, marking the country’s participation for the first time since 1972. The long process of negotiating this breakthrough has been cited as an example of successful global health diplomacy. This paper analyses this negotiation process, drawing on government documents, formal representations from both sides of the Taiwan Strait, and key informant interviews. The actors and their motivations, along with the forums, practices and outcomes of the negotiation process, are detailed. While it is argued that non-traditional diplomatic action was important in establishing the case for Taiwan’s inclusion at the WHA, traditional concerns regarding Taiwanese sovereignty and diplomatic representation ultimately played a decisive role. The persistent influence of these traditional diplomatic questions illustrates the limits of global health diplomacy.
Keywords: Taiwan; World health organization; World health assembly; Global health diplomacy